Clinical Phenotype of Fucosidosis in Cuba - Víctor Jesús Tamayo Chang; George Alberto Pérez Benítez (Revista Finlay)
Foundation: fucosidosis is a rare disease, lysosomal storage, with a wide spectrum of clinical findings. In Cuba patients have only been reported in the Holguín province. Objective: characterize the clinical phenotype of fucosidosis in Cuba. Method: a case series study was carried out, for which the clinical and genetic histories of patients with α-L-fucosidase enzyme activity in leukocytes were analyzed, quantified by spectrofluorimetry 30 % lower than the activity of healthy controls. The behavior of clinical variables related to the onset, evolution and conclusion of the disease was described and the patients were classified according to clinical types. To describe the variables, the statisticians were used: absolute frequency, percentage, ratio and proportion. The arithmetic mean was used as a statistician of central tendency and as a statistician of dispersion: the standard deviation. Results: hurleroid facies, neurological and physical development impairment, joint contractures and skeletal deformities were the most frequent clinical manifestations in the 19 diagnosed cases. 84.2 % of patients presented angiokeratoma, and in 52.7 % there was delay in psychomotor development that began in infancy and rapid neurodegeneration, with loss of motor and language skills before the age of five. 42.1 % of patients died between 10 and 20 years of age. Conclusions: despite the predominance of early onset with early delay in psychomotor development and rapid neurodegeneration, the clinical phenotype of fucosidosis behaved as a continuous spectrum of severity, was the most frequent a clinical form of intermediate progression with death during the second decade of life and presence of angiokeratoma.